Patrimônio à deriva? Revisitando o tombamento no centro de Goiânia - Morais, Vitor de Souza (2023)
In the 20th century important questions and documents were formulated in the field of heritage practices stimulated by theories and international conferences aimed at protecting assets with historical and artistic values. These practices echoed in the creation of heritage preservation bodies and in the elaboration of guidelines for this purpose. In this research, the process of listing buildings in Brazil is debated, having the central sector of Goiânia as a study. The city, designed in the 1930s, had part of its assets listed in 2003 by Iphan. The selection of these assets seems to be based on the official narrative, corroborating only one side of the political discourse at the time, guided by the ancient “scholarly values” of the monuments and oblivious to the involvement of the community. A relationship that highlights, in addition to the problem of choosing assets to consolidate a single story, a paradoxical condition that involves the different meanings of what is read as heritage by the sealing bodies and how these assets seem to be abandoned after the action. This phenomenon is discussed in light of definitions of heritage, history, memory and modernity, confronting the Process of Listing of the Collection of Goiânia, as a mechanism for preserving and recognizing the historical and cultural values of this part of the city. As a methodological support, bibliographical research was used to review the conceptual definitions about heritage, preservation, the institution of protection bodies in the Brazilian context and the contextualization of the problem in Goiânia. The documentary analysis was used from the Listing Process 1.500-T-02, as the primary source of the granting of architectural assets, which reveal the values recognized by the public authorities as heritage in the city. Interviews were carried out with technicians and specialists who participated in the elaboration of the Listing Dossier, and with others who work in the instances of preservation of these assets, in order to understand the role of each entity, in view of the patrimonial condition. The investigation in the Central Sector took place based on research in local newspapers and periodicals, in order to contrast the processes of renovation, listing and the current condition of the referred assets, associating them with the theoretical formulation carried out in the first moment. Investigation that provided insight into the lack of dialogue between protection instances, as well as the lack of attribution of specific, social uses that integrate the goods into a routine of urban life, providing, in most of the city’s-built assets, a drift asset.